Care pathways in the transition of patients between district psychiatric hospital centres (DPCs) and community mental health services - Sather, Eva W.; Svindseth, Marit F.; Crawford, Paul; Iversen, Valentina C. (Wiley, 2018)
Rationale, aims, and objectives: Patients with mental health problems experience numerous transitions into and out of the hospital. Primary care providers have mixed success in identifying and managing patients' needs. This study explores health personnel’s experience of care pathways in patient transition between inpatient and community mental health services. Method: A descriptive qualitative design was chosen. Four focus group interviews with twelve informants from seven different communities were conducted. Interviews were analyzed thematically. Results: Two main themes were identified: integrated care and patient activation. The participants shared their experiences on topics that can affect smooth care pathways in mental health. Six promoting factors were identified for successful patient transition: opportunities for information sharing, implementation of systematic plans, use of e-messages, around-the-clock care, designating one responsible health person in each system for each patient, and the involvement of patients and their families. The following barriers were all found to impede the patients’ transition between levels of care: the lack of a single responsible person at each health care level, insufficient meetings, the absence of systematic plans, difficulties in identifying the right staff at different levels, delays in information sharing, and the complexity of welfare systems negatively affecting patient dignity. Conclusions: Systems and procedures should be developed to ensure clear responsibilities and transparency at each stage of the pathways of care. A single person should take charge of ensuring sufficient connection and communication between inpatient and community mental health services. Finally, both patient and staff in community services should be linked through a direct telephone number with around-the-clock availability.